Chlorophylls, lutein and β‐carotene play great but different roles in colour of rapeseed oil. (1st July 2022) - Yao, Yingzheng; Xuan, Pu; Xiong, Wei; Zhao, Ling; Xu, Xia; Liang, Qiang
Abstract: Natural colourants have great effects on the colour of vegetable oil. A series of colourant–oil simulation systems were constructed to study the effects of chlorophyll, lutein and β ‐carotene and their interactions on the colour of rapeseed oil. CIE L * a * b * and Lovibond RYBN colour codes were used to evaluate the colour of the simulation systems. There were good negative linear correlations between the concentrations of the three natural colourants and L * value in both single colourant–oil and two colourants–oil simulation systems. Chlorophyll had greater effect on lightness of rapeseed oil than lutein and β ‐carotene. The contribution of the two carotenoids to the yellow colour was greater than that of chlorophyll. Lutein and β ‐carotene contributed positively to the red colour of rapeseed oil. They had superposition effect on colour of rapeseed oil, and β ‐carotene might contribute more to the colour than lutein. It provided a method to evaluate the contribution of colourant to the colour and a possibility to regulate oil colour in edible oil industry. Abstract :